Health Behavior Theory to Enhance eHealth Intervention Research in HIV: Rationale and Review - Simoni, Jane M. (Curr HIV/AIDS Rep, 2018)
PURPOSE OF REVIEW: Optimal design and evaluation of eHealth interventions requires the specification of behavioral targets and hypothesized mechanisms of action – both of which can be enhanced with the use of established health behavior theories (HBTs). In this paper, we describe the major HBTs and examine their use in studies of eHealth interventions for HIV prevention and treatment, and assess the contribution of HBT in developing and evaluating eHealth interventions. RECENT FINDING: Based on our review of the literature, we argue the field can benefit from more systematic selection, application and reporting of HBT. We highlight theories specifically designed for eHealth and describe ways that HBT can be used by researchers and practitioners to improve the rigor and impact of eHealth interventions for individuals living with or at risk for HIV. SUMMARY: This brief overview of HBTs and their application to eHealth intervention in HIV research has underscored the importance of a theoretically intentional approach. The theory should be used to inform the design of the eHealth intervention; the intervention should not determine the theory. A theory-driven iterative model of eHealth intervention development may not only improve our repertoire of effective strategies but also has the potential to expand our theoretical and empirical knowledge of health behavior change.